Effectiveness of various radiofrequency ablation catheters in the treatment of typical atrial flutter. (3rd October 2022) - Gorantla, A; Alsaiqali, M; Sivakumar, S; Francois, J; Freytes-Santiago, L; Jallad, A; Budzikowski, A
Abstract: Introduction: Although ablation of typical atrial flutter (AFL) can be easily achieved with radiofrequency energy (RF), there are no studies that compare effectiveness of different ablation catheters. Our study aimed to compare the effectiveness of various types of ablation catheters in the treatment of AFL. Methods: We analysed patients with AFL who underwent RF ablation by a single operator at our institution. Successful ablation was evidenced by presence of bidirectional conduction block (trans-isthmus conduction time ≥130 ms, or doubling of baseline conduction time, or presence of double potentials ≥90ms). Logistic regression was used to compare success rate and linear regression to compare lesion time. Results: Out of the 222 patients, only 6 patients did not meet success criteria (2.7%). Catheters used were 8 mm tip in 16 patients, internally irrigated (Chili II Boston Scientific) in 47 patients, externally irrigated (non-force sensing) catheters (CoolPath, Abbott) in 40 patients. Externally irrigated force sensing catheter (Tacticath, Abbott) was used with >10 gm of force and (LPLD) setting (30W-45°C-60 sec) in 50 patients, and high-power short duration (HPSD) setting (50W-43°C −12 sec, ) in 70 patients. No complications were encountered. Catheter type had no statistically significant association with ablation success. In terms of lesion time, HPSD catheter statistically significantly shortened lesion time by 758.3s, [CI −1128.29, −388.35s] followed by LPLD by 419.0s [CI −808.49, −29.47s]. Table 1 shows the lesion time difference for the catheters used as compared with 8 mm tip. Conclusions: Typical atrial flutter radiofrequency ablation procedure had a high success rate, not influenced by type of ablation catheter. Contact force ablation catheter on HPSD is associated with shorter total lesion time. Funding Acknowledgement: Type of funding sources: None.